Weiterentwicklung diagnostischer Verfahren zur Analyse der Anschlagtechnik Stehend im Biathlonschießen - Siebert, D.; Espig, N. (Leipziger Sportwissenschaftliche Beiträge, 2011)
The importance of the shooting performance in relation to the complex performance in biathlon is increasing due to the introduction of new competition disciplines. As a result, there is a need for further knowledge of performancerelated factors in the discipline of shooting. The authors identify specific deficits in the knowledge about the relationship between body sway, various body angles and shooting posture as well as their influence on the muzzle movements in the moment of shooting. The article provides an overview of new ways in analyzing performance in biathlon shooting. Further, selected research results will be presented.